Target Product Profile (TPP) for Chagas Disease Point-of-Care Diagnosis and Assessment of Response to Treatment - Porrás, Analía I (2015)
Fil: Porrás, Analía I. Pan American Health Organization, Regional Office of the World Health Organization, Washington, D.C.; Estados Unidos.